Penguatan Nilai-Nilai Islam pada Remaja sebagai Tindak Prevetif terhadap Gempuran Prilaku Seksualitas Ala Barat - Andriani, Ana; Bramasta, Dhi; Wijarnako, Raden Beny (Universitas Pahlawan Tuanku Tambusai, 2025)
Islamic values are often considered to hinder self-development, a mistaken assumption that deviates from the true teachings of Islam. Learning religion from an early age actually increases an individual's capacity to grow wiser, more analytical, and more resilient in facing problems, and to distinguish between benefits and harms. This research in Bojongsari Village, Banyumas, examines the strengthening of Islamic values in adolescents as a preventive strategy against the influence of Western-style sexual behavior that is increasingly prevalent in the era of globalization. Using a qualitative approach, the study results show that internalizing faith, morals, and worship successfully forms a moral barrier. Support from family, religious leaders, and educational institutions through religious studies, spiritual guidance, and contextual religious literacy has proven effective in shaping a strong Islamic character. Thus, strengthening Islamic values is a strategic step to ensure adolescents maintain noble morals and are not easily eroded by cultures that conflict with religious teachings.